A three-dimensional model of MSME performance: an agenda for further research - Maria Rio Rita; Andrew Thomas Thren (Universitas Negeri Surabaya, 2019)
This paper discusses company performance measurement literature as well as surveys the development of the newest literature about this topic. The purpose of this research is to produce a new measurement of MSME performance by inputting the entrepreneurial performance element, besides the financial measurement element and the market element. Qualitative research with a meta-synthesis method was used in this research to produce a new and wider viewpoint and understanding of the MSME performance measurement dimension. This entrepreneurial dimension can supplement the previously developed company performance measurement indicators. This study provides a performance measurement model modification that can be applied in Micro, Small, and Medium-sized Enterprises (MSMEs). KeywordsMSMEs; performance; entrepreneurial dimension; financial dimension; market dimension